The effect of price regulation on the performances of industrial symbiosis: a case study on district heating - Sacchi, Romain; Ramsheva, Yana Konstantinova (International Journal of Sustainable Energy Planning and Management, 2018)
This study of the district heating system of Aalborg (Denmark) analyses how fiscal instruments affect the extent excess heat recovery helps reduce the carbon footprint of heat. It builds on a supply-and-demand framework and characterizes the changes in excess heat supply with consequential life cycle assessment in reference to one gigajoule distributed. The heat supply curve is defined through ten scenarios, which represent incremental shares of excess heat as the constraints of the said legal instruments are lifted. The heat demand curve follows the end-users’ response to price changes. The most ambitious scenario doubles the amount of excess heat supplied and reduces the heat carbon footprint by 90% compared to current level, for an end-user price increase of 41%. The price increase results from a higher supply of excess heat at a higher price and an unchanged purchase cost from the coal-fired CHP plant despite a lower supply. This highlights the necessity of a flexible supplier when the share of recovered excess heat is high.